Assessment of seasonal variations of teal carbon in palustrine wetlands of the grassland biome : a case study of Chrissiesmeer, Mpumalanga Lakes District, Mpumalanga Province, South Africa - Van Deventer, Heidi (University of Pretoria, 2023)
Dissertation (MSc (Geoinformatics))--University of Pretoria, 2023.